2017
DOI: 10.1155/2017/9154934
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Oxidation Kinetics and Oxide Scale Void Position of Ferritic-Martensitic Steels in Supercritical Water

Abstract: Exfoliation of oxide scales from high-temperature heating surfaces of power boilers threatened the safety of supercritical power generating units. According to available space model, the oxidation kinetics of two ferritic-martensitic steels are developed to predict in supercritical water at 400 ∘ C, 500 ∘ C, and 600 ∘ C. The iron diffusion coefficients in magnetite and Fe-Cr spinel are extrapolated from studies of Backhaus and Töpfer. According to Fe-Cr-O ternary phase diagram, oxygen partial pressure at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…To reduce carbon emissions, it is desirable to improve the efficiency of the steam-generating power plants by increasing the operating steam temperature and pressure, such as in the ultra-supercritical coal-fired power plants [7,8] and supercritical water-cooled nuclear reactors [9][10][11]. With the increase of operating temperatures (>600 ºC), the growth of oxide film on the F-M steels is significantly enhanced [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The consequences of the thickening and failure of the surface oxides are of increasing concern in these steam-generating power plants.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce carbon emissions, it is desirable to improve the efficiency of the steam-generating power plants by increasing the operating steam temperature and pressure, such as in the ultra-supercritical coal-fired power plants [7,8] and supercritical water-cooled nuclear reactors [9][10][11]. With the increase of operating temperatures (>600 ºC), the growth of oxide film on the F-M steels is significantly enhanced [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The consequences of the thickening and failure of the surface oxides are of increasing concern in these steam-generating power plants.…”
Section: Introductionmentioning
confidence: 99%
“…At lower temperatures (less than 400 °C), magnetite has a unit cell of 32 O 2− ions into which are placed 8 Fe 3+ ions at tetrahedral sites and 8 Fe 2+ + 8 Fe 3+ ions at octahedral interstices (i.e., inverse spinel structure), while a certain proportion of Fe 2+ goes into the tetrahedral interstices, more like a normal spinel, with an increase in temperature [46]. Generally speaking, the principal defects are cation vacancies and iron interstitials, which is the basic supporting theory for the off-stoichiometric structure, as well as for the metal transport within this bulk oxide, while the oxygen sublattice remains relatively fixed because its defects have higher energy [11,46,47,48]. However, for oxide formation at the metal/oxide interface, and noting that the oxide grows into the metal, which is correct for the growth of the inner layer, then oxygen vacancies are always produced at the metal/inner layer interface leading to the inward transport of oxide ions, and hence are always present in the barrier layer regardless of their energy [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…The critical boundary oxygen partial pressure (pc,o2) generally increases with temperature. Taking magnetite as an example, which has been studied extensively as a function of oxygen partial pressure, the critical boundary oxygen partial pressure (pc,o2) is ~10 −6 atm at 1200 °C [48], ~10 −8.3 atm at 1000 °C [46], ~10 −20 atm at 600 °C [11], ~10 −25 –10 −22 atm at 500 °C [11,46], and ~10 −30 atm at 400 °C [11]. Previous studies have suggested that the rate-controlling step in the corrosion of ferritic-martensitic steels in SCW is the outward diffusion of iron and that the inner layer generally plays the role of the protective barrier layer [7,8,10,12,30,33,51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations